Relationship of microparticles to progenitor cells as a measure of vascular health in a diabetic population - Curtis, Anne M.; Zhang, Lifeng; Medenilla, Elizabeth; Gui, Ming; Wilkinson, Patrick F.; Hu, Erding; Giri, Jay; Doraiswamy, Vijay; Gunda, Sampath; Burgert, Mark E.; Moore, Jonni S; Edelberg, Jay M.; et al. (Cytometry. Part B, Clinical cytometry, 2010)
Objective: Quantitative measures are needed to identify diabetic patients at higher risk for CV events. Cell‐derived microparticles (MPs) are submicron membrane vesicles released from activated cells that are indicative of cell damage. Progenitor cells (PCs) including proangiogenic cells (PACs), often termed endothelial progenitor cells (EPCs), are mediators of reparative capacity. We examined whether the relationship of MPs to PCs/PACs could be used as an improved and clinically feasible index of vascular pathology. Methods and Results: Plasma samples were collected from patients with early‐stage (ES, Diagnosis < 1year) and long‐term (LT, Diagnosis > 5 years,) Type 2 diabetes and compared with age related healthy subjects (H). PC and MP subtypes were measured by a combination of flow cytometry and ELISA‐based methods. The ratio of procoagulant MPs/CD34+ PCs proved a valuable index to distinguish between subject groups (P = 0.01). This index of compromised vascular function was highest in the LT group despite intensive statin therapy and was more informative than a range of soluble protein biomarkers. Conclusions: This is the first report of a relationship between MPs and PCs in Type 2 diabetes. This ratio may provide a quantitative and clinically feasible measurement of vascular dysfunction and cardiovascular risk in patients with diabetes. © 2010 International Clinical Cytometry Society